Răspuns:
Explicație pas cu pas:
a) 2^3×2^4=2^7
b) (-3)^2×(-3)^6= (-3)^8
c) (-4)×(-4)^2= (-4)^3
d) 5^2×5^4×5^6= 5^12
e) 7×7×(-7)= (-7)^3
f) X×X^2×X^3×X^4×X^5= X^15
g) (-2)^4:(-2)^3= (-2)
h) 3^6:3^2= 3^4
i) (-4)^10:(-4)^7= (-4)^3
j) (-20)^10:(-20)^5:(-20)^5=(-20)^5:(-20)^5=1
k) [(2)^2]^3= 2^6
l) (5^1)^0=1
m) [(-3)^5]^2=(-3)^10
n) [(-7)^3]^5 = (-7)^15
o) [(-1)^7]^4=(-1)^28
p) [2^2×(-3)^3]^2= 2^4×(-3)^6
q) [(-2)×(+3)^2]^3=(-2)^3×(+3)^6
r) (-2)^7×2^5=-(2)^12
s) [(+6)(-2)(-3)]^2=(6^2)^2=(6)^4
t) [-3×(+7)^2]^0=1
u) (a^2×b^2×c^2)^4= (a^8×b^8×c^8)